Admission trends at Red Cross War Memorial Children's Hospital, Cape Town: 2004 to 2013 - Isaacs, Yumnah (Department of Public Health and Family Medicine, 2017)
Background: Hospital database research has the potential to provide useful insights into health systems functioning, population health, clinical conditions and epidemiological trends thereof. This type of research is routinely done in countries that have large national hospital databases where results are usually extrapolated to the national population. South Africa does not have a national hospital database, but individual healthcare institutions, such as the Red Cross War Memorial Children's Hospital (RCCH) in Cape Town, collects routine patient data in a computerised database that if tapped should yield valuable information about child health of the catchment population as well as of the functioning of that health institution. Methods: Selected data from the RCCH database were converted into spreadsheet format and then exported into a statistical programme, Stata. Variables included patient demographic details, ICD-10 diagnostic codes, length of hospital stay and outcomes at discharge. Stata was used to clean and code the data and perform basic descriptive analyses of contained variables. Medians and interquartile ranges described numerical variables. Frequencies, proportions and percentages described categorical variables. Appropriate tests of statistical significance were performed where applicable. Admission and mortality trends were analysed across a decade and common conditions were explored. Findings and Conclusions: Overall admissions to RCCH increased by 9.3% across a decade while the number of new patients decreased by 8.6%, indicating an increase in readmissions. In-patient mortality decreased consistently across a decade despite an increase in admissions, which suggests an improvement in quality of care. The median ages of admissions and deaths increased across the decade, which correlates with less HIV and improved management thereof. Infections remain the commonest causes of in-hospital mortality. Admissions and mortality for diarrhoea and pneumonia displayed a consistent decline across 6 years corresponding with the introduction of new vaccines; however, diarrhoea and lower respiratory tract illness remained the commonest causes of medical admission. Injuries were the commonest reason for surgical admissions. Computerised hospital databases contain useful information for healthcare research.